Reconstruction of Islamic Law: An Appraisal of Basic Principles - Khan, Hafiz Abdul Basit (Journal of Islamic and Religious Studies, 2020)
Rapid development in all fields especially in economic and medical sciences has made the attention of Muslim jurists turned towards a reframing of Islamic legal theory. Dr. Waḥaba al-Zuḥaylī and Dr. Jamāl Al-dīn Aṭiyyah have left behind them rich literature in this regard. Other numerous Muslim jurists have also laid down some principles for reshaping Islamic jurisprudence. Applying the analytical method of research, the author initially investigated the leading principles recommended by these scholars for this reconstruction. He then has very briefly described five basic principles that were established by these scholars; Collective ijtihād in which a group of jurists make their best efforts to bring a solution of problems faced by Muslims is assumed to be very effective and more beneficial than individual ijtihād. Combining of maḍāhib, which is termed as Talfīq, is advocated by a group of contemporary jurists to develop an exclusive circle for Muslims to practice Sharī’ah in a specific field. Islamic banking is the most appropriate example of this principle. Both types of ijtihād: derivative and purposefulness must be applied parallel. Where more than one viewpoint in an injunction is found in one school of fiqh, only that one should be preferred which ensures fulfillment of the maṣlaḥah that has been observed in that injunction. The codification of fiqh literature will also be helpful in the implementation of Islamic law. These five principles can make Shariah practicable and implantable in the modern world where Muslims are not holding the field.